Implementasi Website Penilaian Kinerja Paramedis pada Rumah Sakit - Palasara, Nicodias; Anggraeni, Diah Ayu; Qomaruddin, M (JURIKOM (Jurnal Riset Komputer), 2020)
Performance appraisal that still uses manual calculations and paper media, will use a lot of paper and archiving stacked files and often there are errors or unclear writing so that they do not get the right assessment results on target. As one of the means of public health service providers are required to improve the quality and professionalism in terms of health services, one of which is in the scope of health workers such as paramedics. Overcoming this, a significant increase in the number of paramedics in hospitals must be in line with good management by human resources officers, in order to improve the quality of health services. Then the implementation of the paramedic performance appraisal website at the hospital is one good solution to make it easier to overcome the problem. In this study created a website to support the paramedic performance evaluation. In making a website using the waterfall method, whose function can accelerate the results and quality of the website. Computerized performance appraisal systems run better and more efficiently than manual systems and can minimize paper usage and data accuracy